Roman historical drama : the Octavia in antiquity and beyond - Kragelund, Patrick (Oxford University Press, 2016)
This title provides a comprehensive interpretation of ancient historical drama in relation to the 'Octavia', revealing how the play mirrors the genre's traditions by mixing formats and stock characters from traditional tragedy with elements drawn from new developments of the Hellenistic and Roman stage